Enhancing Diagnostic Accuracy in Orthodontics: Calibration and Validation of a New Tool for Dental Arch Measurements—Pilot Study - Andrada-Nicoleta Nikolajević-Stoican; Vlad Tiberiu Alexa; Daniela Jumanca; Atena Galuscan; Roxana Oancea; Dacian Lalescu; Camelia Szuhanek (Applied Sciences, 2024)
(1) Background: In the pursuit of enhancing diagnostic precision and treatment planning in orthodontics, accurate measurements in dental study casts of the different parameters of the dental arch stands as a critical element. Measurements such as dental arch perimetry, arch length or intermolar distance play a key role in achieving optimal results in orthodontics. Therefore, the aim of this study is to develop, calibrate and verify a new tool for determining dental arch measurements and to compare these measurements, carried out with the newly fabricated instrument, to two other conventional measurements used in orthodontics. (2) Methods: The study used 40 dental study casts for measuring the three mentioned arch parameters. The measurements were conducted following three methods: with the new instrument, with the help of a digital caliper and with the conventional method using a graduated ruler and metal wire. The difference between the values obtained by measuring with the new instrument and the other two methods was noted out in order to calculate the margin of error. Descriptive statistics, including mean, minimum, maximum, and standard deviation, were computed for all replicates, while normality was assessed using the Kolmogorov–Smirnov and Shapiro–Wilk tests; mean differences were examined using the Friedman test and the Wilcoxon signed-rank test, with statistical significance set at p-values < 0.05. Results: In the case of the arch perimeter measurement, the difference from the conventional measurement was −0.045 mm ± 0.006 and from the digital measurement was 0.025 ± 0.013. The measurement of the anterior arch length results shows that the difference from the conventional measurement was −0.0002 ± 0.014 and from the digital measurement 0.02 ± 0.0006. For the measurement of the intermolar distance of the upper permanent molars, the difference from the conventional measurement was −0.02 ± 0.01 and from the digital measurement −0.02 ± 0.001. The greatest differences were observed in the measurements of the parameter “Arch perimeter”, obtaining an average value of −0.045 ± 0.006 mm between the measurement with the new instrument and that with the conventional method using graduated rulers, as opposed to a value of 0.025 ± 0.013 for the difference from the digital measurement. Conclusions: the values obtained using the proposed instrument closely align with those obtained through traditional measuring methods like the graduated ruler and metal wire, demonstrating comparable results. Additionally, the measurements closely match those achieved through digital measurement using electronic calipers, showcasing the instrument’s accuracy in comparison to established techniques.